Uniqueness Deposit of Sediment on Floodplain Resulting From Lateral Accretion on Tropical Area : Study Case at Kampar River, Indonesia - Yuskar, Yuniarti; Choanji, Tiggi (Journal of Geoscience, Engineering, Environment, and Technology, 2017)
Kampar rivers has a length of 413 km with average depth of 7.7 m and width of 143 m. Sixty percent of  this rivers are meandering fluvial system which transport and deposit a mixture of suspended and bed-load (mixed load) along low energy. River channel that moving sideways by erosion is undergoing lateral migration and the top of the point bar becomes the edge of the floodplain and the fining-upward succession of the point bar will be capped by overbank deposits of Kampar River. Along the Kampar Rivers, there are more than 60% of ï¬oodplain sediments and almost all of the ï¬oodplain formed by bend migration on the suspended-load channels of Kampar watershed. This formation consist of succession of fine to medium sand and silt/mud, with root traces, that form as drapes on the prograding bank. These beds dip mostly channel wards and quickly wedge out as they grade up and onto the ï¬oodplain. The depositional model is presented showing how lateral accretion can make a signiï¬cant contribution to the preservation of ï¬ne-grained within channel deposits in contemporary ï¬oodplains. The examples presented here demonstrate that analogues to ancient point-bar deposits containing alternating sandstone and shale sequences are common in the low-energy ï¬uvial environments of Riau rivers especially Kampar rivers.